KARAKTERISASI SENYAWA MINYAK ATSIRI DALAM MINYAK KAYU PUTIH DI PABRIK GELARAN YOGYAKARTA DENGAN FTIR - Pratiwi, Deby; Fitriyani, Dwi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Eucalyptus plants (Melaleuca cajuputi) are one of the essential oil-producing plants that are important for the essential oil industry in Indonesia, the potential of wood oil plants in Indonesia is quite large, starting from the Maluku, Bali, and Java areas as one of the ingredients for health or pharmaceutical products. The purpose of this study is to determine the content of essential oils in eucalyptus oil using FTIR. To determine the characteristics of essential oil compounds in eucalyptus oil is carried out by characterizing FTIR from the tests carried out, it is hoped that the characterization of essential oil compounds in eucalyptus oil can be obtained. The results of the study contain eucalyptus oil containing the main component, namely 1,8-sineol. This is indicated by the appearance of longitudinal vibrations in the functional groups in the function groups -CH2 at wave numbers 1463.27 and 1361.15 cm-1, -CH3 at wave number 1361.15 cm-1, C-H alkanes at wave numbers 2965.27 and 2920.29 cm-1, and C-O at wave numbers 1214.72, 1167.29, and 1078.61 cm-1 there are 1,8-sineol compounds [2]. The C-O group at wave numbers 1214.72, 1167.29, and 1078.61 cm-1 is an ether group. The quality of eucalyptus oil is determined by the content of sineol, the higher the sineol content, the higher the quality value.